Assessment of non‐lobe‐specific lymph node metastasis in clinical stage IA non‐small cell lung cancer. Issue 7 (17th June 2019) - Zhang, Zhirong; Miao, Jinbai; Chen, Qirui; Fu, Yili; Li, Hui; Hu, Bin
Abstract : Background: The rationality of selective mediastinal lymph node dissection based on lobe‐specific metastasis is still controversial. The correlation of lymph node metastasis in lobe‐specific lymphatic drainage regions (LSDRs) and non‐LSDRs has not been widely reported. The purpose of this study was to investigate the variables affecting nodal metastasis in non‐LSDRs and to further evaluate the rationality of selective lymphadenectomy in clinical stage IA non‐small cell lung cancer (NSCLC) patients. Methods: The clinicopathological information of 316 patients with clinical stage IA NSCLC who underwent lobectomy with systematic lymph node dissection between June 2014 and June 2018 was retrospectively collected for analysis. Results: The overall lymph node metastasis rate was 19.3%. For 35 patients with positive LSDR lymph nodes, the non‐LSDR lymph node metastasis rate was 31.4%. Only one patient (0.4%) among 281 patients with negative LSDR lymph nodes had nodal spread in non‐LSDRs. Univariate analysis identified that solid consistency, worse differentiation, and positive status in LSDRs were unfavorable predictive variables of lymph node metastasis in non‐LSDRs. Multivariate analysis showed that nodal metastasis in LSDRs was the only independent predictor of nodal involvement in non‐LSDRs ( P < 0.001). Conclusion: For patients with clinical stage IA NSCLC, non‐LSDR lymph node metastasis mainly depends on the involvement of the LSDR lymph node. Our observations may indicate the potential implications for the reasonable management of lymphadenectomy in stage IA NSCLC patients.